Estimation of Nitrite (NO2−), Phosphate (PO34−) and Sulfate (SO24−) in Soil Samples of Kathmandu Valley and Western Nepal - Parthak, Arvind; Kumal, Srijana; Mishra, Pawan Kumar (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
Title: Estimation of Nitrite (NO2−), Phosphate ( PO34− ) and Sulfate ( SO24− ) in Soil Samplesof Kathmandu Valley and Western Nepal Soil is a dynamic resource that interacts with the ecosystems such as water, air, flora and fauna that influence plant, life on earth. Soil fertility largely affects agriculture, plant and animal productivity. It requires to preserve water and air quality to sustain human health and habitation. Nitrite, phosphate, and sulfate of soil samples from 10 different places were estimated. Nitrite was analyzed by the addition of benzidine, hydrochloric acid solution, dimethylaniline followed by the addition of NaOH, a pink red colored azo dye was formed and was measured spectrophotometrically in the range of 0.068 to 0.213 mg/L. At a pH of 8.5 the available phosphates were extracted with sodium bicarbonate solution and acidified with H2SO4. In the presence of ammonium molybdate and hydrazine hydrate, a light blue colored ammonium phosphomolybdate complex was formed and was measured by spectrophotometer in the range of 0.158 to 0.279 mg/L. In presence of excess of BaCl2, sulfate ion was then determined by turbidimetry method in the range of 0.130 to 0.271 mg/L.